Elemental substitution effects in multiferroic R Fe2O4 (R: rare earths). Issue 6 (30th March 2015) - Yoshii, Kenji; Funae, Takashi; Mizumaki, Masaichiro; Ejiri, Hiroki; Ikeda, Naoshi; Saitoh, Hiroyuki; Matsumura, Daiju; Tsuboi, Nozomu; Wakita, Kazuki; Yamada, Akira; Shirakata, Sho; Wada, Takahiro; et al.
Abstract We report the effects of elemental substitutions in multiferroic R Fe2O4 (R: Y, Ho‐Lu, In). The substitution by nonmagnetic Ga3+ at the Fe site, which has not been reported so far, shows a drastic decrease in the ferrimagnetic transition temperature (TN). This is plausibly owing to the suppression of magnetic interactions between Fe ions, based on our previous results of other substituted systems such as R FeCoO4. Dielectric constants near room temperature were comparable to those of R Fe2O4. The suppression of dielectric loss in this system is suitable to application. The R ‐site substitution was also attempted by the large R3+ ions such as Dy3+. The solubility limit was up to ∼10% of R ions. TN was raised by 5‐10 K for Dy3+ substitution. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)